An Integrative Approach to Understanding Flight Crew Activity. (December 2013) - Hutchins, Edwin; Weibel, Nadir; Emmenegger, Colleen; Fouse, Adam; Holder, Barbara
In this paper, we describe an integrative approach to understanding flight crew activity. Our approach combines contemporary innovations in cognitive science theory with a new suite of methods for measuring, analyzing, and visualizing the activities of commercial airline flight crews in interaction with the complex automated systems found on the modern flight deck. Our unit of analysis is the multiparty, multimodal activity system. We installed a variety of recording devices in high-fidelity flight simulators to produce rich, multistream time-series data sets. The complexity of such data sets and the need for manual coding of high-level events make large-scale analysis prohibitively expensive. We break through this analysis bottleneck by using our newly developed integrated software system called ChronoViz, which supports visualization and analysis of multiple sources of time-coded data, including multiple sources of high-definition video, simulation data, transcript data, paper notes, and eye gaze data. Four examples of flight crew activity serve to illustrate the methods, the theory, and the kinds of findings that are now possible in the study of flight crew interaction with flight deck automation.